2016
DOI: 10.3390/ijms17101727
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations on Structure–Function Relationships of Matrix Metalloproteinase-1

Abstract: Matrix metalloproteinase-1 (MMP-1) is one of the most widely studied enzymes involved in collagen degradation. Mutations of specific residues in the MMP-1 hemopexin-like (HPX) domain have been shown to modulate activity of the MMP-1 catalytic (CAT) domain. In order to reveal the structural and conformational effects of such mutations, a molecular dynamics (MD) study was performed of in silico mutated residues in the X-ray crystallographic structure of MMP-1 complexed with a collagen-model triple-helical peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…40 The DCCA is used to visualize which residues play a role in correlated motions that occur between different components of the protein structure. 41 The level of correlation between each Cα atom can be quantified and visualized on a plot, with correlations ranging from +1 to −1, indicating a strong positive to a negative correlation. This allows the identification of regions in the protein, showing correlated motion in the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…40 The DCCA is used to visualize which residues play a role in correlated motions that occur between different components of the protein structure. 41 The level of correlation between each Cα atom can be quantified and visualized on a plot, with correlations ranging from +1 to −1, indicating a strong positive to a negative correlation. This allows the identification of regions in the protein, showing correlated motion in the simulation.…”
Section: Methodsmentioning
confidence: 99%
“…A Transwell experiment ( Wang 2018 ) proved that when the MMP1 gene was silenced, the invasion and migration ability of BRCA was significantly reduced. In addition, collagen is also an important part of ECM ( Ma et al, 2016 ), while MMP1 can degrade type I, II and III collagen ( Singh et al, 2016 ). This study confirmed that MMP1 participated in collagen metabolism and the degradation of extracellular matrix tissue, promoting cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The MMPs are considered the most important proteolytic enzymes in tumor invasion and metastasis, especially MMP-9 [19]. The MMP-9 promotes tumor invasion and metastasis through two mechanisms: by degrading ECM and the basal plasma membrane of the vascular wall, and by promoting capillary angiogenesis of the tumor [20]. It was found that there are binding sites for transcription factors such as NF-κB in the promoter region of human MMP-9.…”
Section: Discussionmentioning
confidence: 99%